The analysis of the soliton-type solutions of conformable equations by using generalized Kudryashov method - Kaplan, Melike; Akbulut, Arzu (Springer Science and Business Media LLC, 2021)
Abstract
This research article is dedicated to applying the generalized Kudryashov method in order to acquire new exact and soliton-type solutions of the conformable Burgers' equation and Wu-Zhang system with conformable derivative.